Ostrich (Strutio camelus) meat protein quality and digestibility - Oliveira, T. C.; Reis, L. S. (Brazilian Journal of Poultry Science, 2008)
The purpose of the study was to evaluate ostrich meat protein quality, as its consumption has significantly increased in the last few years in Brazil. Male Wistar rats were distributed in groupe of six elements. The standard group received a casein-based diet, the control group received a protein-free diet, and the experimental group received ostrich meat diet as protein source. The evaluated biological parameters were protein efficiency ratio (PER), net protein ratio (NPR), net protein utilization (NPU), and true digestibility (TD). There were differences (p<0.05) among treatment groups for all evaluated biological parameters. Mean true digestibility values were 92.12% and 75.77% for casein and ostrich meat, respectively.
Keywords: Casein; Digestibility; Ostrich meat; Protein quality